Stamped pottery from Tigranakert in Artsakh - Gabrelyan, Armine (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The stamped pottery is of great significant for the research of the material culture of the antique (1st century BC - 3rd century CE) period of Tigranakert city in Artsakh, former Nagorno-Kharabakh Autonomous Region. It is distinguished by the variety of forms and styles, including coloured, black, white, polished, stamped, and decorative carved examples. The present article aims at presenting diverse traits of the stamped type pottery in Tigranakert.